Gangguan Mental Emosional dan Kesepian pada Mahasiswa Baru - Prasetio, Clement Eko; Rahman, Tiffani Amalia; Triwahyuni, Airin (Mediapsi, 2019)
In the transition period from high school to college, freshmen have to deal with the new environment, which makes them vulnerable to experience symptoms of mental  disorders. The aim of the current study was to examine the role of loneliness as a predictor of symptoms of mental disorders among freshmen. Using a convenience sampling, 151 first-year undergraduate students from one faculty at Universitas Padjadjaran took part in the current study. The respondents completed a self-report questionnaire consisting of WHO Self-Report Questionnaire (SRQ) to assess symptoms of mental disorders and UCLA Loneliness scale to assess loneliness. The result showed that loneliness significantly predicted  symptoms of mental disorders among freshmen. Theoretical implications of these empirical findings are discussed, as are practical implications highlighting the suggestions for the university stakeholders to implement an intervention that is effective in tackling freshmen’s mental disorders such as social skill training, increasing social support, and increasing probability of social contactPada masa transisi dari sekolah menengah atas ke perkuliahan, mahasiswa harus menyesuaikan diri dengan lingkungan barunya. Akibatnya, pada masa ini mahasiswa sering mengalami gejala-gejala gangguan mental emosional. Tujuan penelitian ini adalah untuk menguji peran perasaan kesepian dalam memprediksi gangguan mental emosional di kalangan mahasiswa baru. Melalui penarikan sampel yang bersifat convenient, sebanyak 151 mahasiswa baru  pada salah satu fakultas di Universitas Padjadjaran berpartisipasi dalam penelitian ini. Metode pengumpulan data menggunakan kuesioner yaitu Self Report Questionnaire (SRQ) untuk mengukur gejala gangguan mental emosional dan UCLA Loneliness Scale untuk mengukur tingkat kesepian. Hasil penelitian ini menunjukkan bahwa kesepian dapat menjadi prediktor gangguan mental emosional pada mahasiswa baru. Implikasi teoretis dari temuan ini kami diskusikan, dan juga implikasi praktis yang menekankan pada pentingnya bagi pihak universitas untuk menerapkan sebuah intervensi yang efektif dalam menangani gangguan mental emosional di kalangan mahasiswa baru, seperti pemberian pelatihan keterampilan sosial, peningkatan dukungan sosial serta kontak sosial